1998
DOI: 10.1006/dbio.1998.9026
|View full text |Cite
|
Sign up to set email alerts
|

Paracrine Induction of Stem Cell Renewal by LIF-Deficient Cells: A New ES Cell Regulatory Pathway

Abstract: The propagation of pluripotential mouse embryonic stem (ES) cells is sustained by leukemia inhibitory factor (LIF) or related cytokines that act through a common receptor complex comprising the LIF receptor subunit (LIF-R) and the signal transducer gp130. However, the findings that embryos lacking LIF-R or gp130 can develop beyond gastrulation argue for the existence of an alternative pathway(s) governing the maintenance of pluripotency in vivo. In order to define those factors that contribute to self-renewal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
76
0

Year Published

1999
1999
2012
2012

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 112 publications
(80 citation statements)
references
References 72 publications
4
76
0
Order By: Relevance
“…Therefore, in order to assess the actual level of gene expression and protein activities in self-renewing -undifferentiated -ES cells, we made use of the IOUD2 ES cell line which expresses the LacZ -neomycin -phosphotransferase fusion gene (beta -geo) driven off the oct-4 promoter (Dani et al, 1998). The promoter of the oct-4 gene is active in undifferentiated ES cells and it is switched off at the onset of differentiation in vitro (Mountford et al, 1994).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, in order to assess the actual level of gene expression and protein activities in self-renewing -undifferentiated -ES cells, we made use of the IOUD2 ES cell line which expresses the LacZ -neomycin -phosphotransferase fusion gene (beta -geo) driven off the oct-4 promoter (Dani et al, 1998). The promoter of the oct-4 gene is active in undifferentiated ES cells and it is switched off at the onset of differentiation in vitro (Mountford et al, 1994).…”
Section: Resultsmentioning
confidence: 99%
“…IOUD2, a feeder-independent ES cell line, was used. IOUD2 cells express the LacZ-neomycin-phosphotransferase fusion gene (beta-geo) driven off the oct-4 promoter (Dani et al, 1998). They were cultured in the presence of G418 (250 mg/ml) in order to kill spontaneously differentiating cells.…”
Section: Cells Media and Inhibitorsmentioning
confidence: 99%
“…Additionally, the increased paracrine growth-factor signalling between ESCs in more three-dimensional, tightly packed colonies on the SCC substrates may also stimulate self-renewal. Dani et al showed that even in the absence of LIF, paracrine factors in ESC colonies can stimulate self-renewal (Dani et al, 1998). Of course, this is also true in EBs, but since EBs are in the region of 300-1000 μm in thickness (compared to approximately 80 μm for colonies on the SCC substrates), other factors such as increased cell migration, nutrient depletion, and distance-dependent paracrine signalling antagonistic to self-renewal may obscure this effect.…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, the lack of a phenotype in the unperturbed embryo suggest that other mechanisms are normally responsible for the maintenance of pluripotent identity. The ability of lif À/À ES cells to self-renew in the presence of neutralizing gp130 antibody provided evidence of an additional pathway for ES cell maintenance (Dani et al, 1998). This ES cell selfrenewal factor (ESRF) was detectable in the conditioned medium produced by a parietal endoderm-like cell line.…”
Section: Molecular Basis For Es Cell Self-renewalmentioning
confidence: 99%